Determinants of Managerial Performance in Muhammadiyah Universities: Innovation and SDG’s 12 - Sarwenda Biduri; Eny Maryanti; Sigit Hermawan; Fadilla Rahmawati; Cicik Suciati (Jurnal Akuntansi, 2024)
This study aims to formulate Determinants of Improving Managerial Performance of Muhammadiyah Universities with Innovation Performance as a Moderating Variable for Achieving SDG's No. 12. The research method used is quantitative method with data collection through questionnaires. The research sample was all employees of Muhammadiyah Universities in East Java. The results showed that Information Technology has no effect on Managerial Performance, Budget Participation has no effect on Managerial Performance, but Total Quality Management (TQM) affects Managerial Performance. Furthermore, Innovation Performance can moderate the effect of Information Technology and Total Quality Management (TQM) on Managerial Performance, but cannot moderate the effect of Budget Participation on Managerial Performance. This study implies that improving the Managerial Performance of Muhammadiyah Universities can be done by implementing Total Quality Management (TQM) and supported by Innovation Performance as a moderating variable. This research is expected to be a reference for further research related to improving Higher Education Managerial Performance.